Identifying Augmented Reality (AR) design component for mural design in Kuala Lumpur - Zulkifily, Muhammad Zahin; Hairul Anuar, Inda Murni; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
This study investigates the design components for enhancing engagement and accessibility of augmented reality (AR) murals in Kuala Lumpur. Augmented Reality (AR) technology within the existing murals can revitalize public areas and bring new interactions to the public. The main objective of this study is to explore the key design elements that make Augmented Reality (AR) effective and to understand how these elements work together to enhance AR experiences. It looks at how the visuals were put together, how users interact with the technology and how AR blends with physical spaces. By implementing content analysis on existing murals in Kuala Lumpur, this study observes the design principles used to achieve immersion and interactivity. The results of the study are to understand the importance of interface aesthetics and user experience, the role of colour, intuitive design experience and space in developing engaging AR experiences. According to the study, integration of these design features can make AR murals more interactive, visually engaging, and culturally significant, offering a stepping stone to developing immersive urban arts. The findings of this research present a definite guideline for the application of Augmented Reality (AR) to revitalize Kuala Lumpur murals to be more accessible and enjoyable for a broader audience.